High-risk early adolescents' perceptions of jail and offender experiences - Folk, Johanna B. (Applied psychology in criminal justice, 2014)
Although a far-reaching phenomenon, little is known about youths' understanding of incarceration or offenders. Using mixed methods, this research assessed 106 youths' (M = 11.54 years; 56.6% girls; 78.3% Black) understanding of jail and offenders. Caregivers reported youth' exposure to the criminal justice system through parental arrest (42.5%) and incarceration (32.4%). Factors found to influence youths' understanding include age, gender, and parental involvement in the criminal justice system. Results from the current study offer a snapshot of high-risk youths' understanding of jail and offenders, as well as some factors that influence them. This information may be useful for those who work with children of incarcerated parents, where misconceptions may influence psychological adjustment and the need for targeted interventions is paramount.